2014
DOI: 10.1073/pnas.1321330111
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase (HDAC) 1 and 2 are essential for accurate cell division and the pluripotency of embryonic stem cells

Abstract: Histone deacetylases 1 and 2 (HDAC1/2) form the core catalytic components of corepressor complexes that modulate gene expression. In most cell types, deletion of both Hdac1 and Hdac2 is required to generate a discernible phenotype, suggesting their activity is largely redundant. We have therefore generated an ES cell line in which Hdac1 and Hdac2 can be inactivated simultaneously. Loss of HDAC1/2 resulted in a 60% reduction in total HDAC activity and a loss of cell viability. Cell death is dependent upon cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 42 publications
(59 reference statements)
13
125
0
Order By: Relevance
“…ChIP-qPCR at the same six ESC and six EpiC enhancers done for BRG1 validated these results and extended them to HDAC2, which is commonly found in a complex with HDAC1 (Lai and Wade, 2011;Jamaladdin et al, 2014) (Figures S5D and S5E). Consistent with a role for FOXD3 in recruiting as well as maintaining HDAC1 at the FOXD3-bound enhancer sites, HDAC1 was not found at the EpiC enhancers prior to FOXD3 binding (compare Figure 6K to 6L).…”
Section: Foxd3 Also Recruits and Maintains Hdac1/2 At Enhancerssupporting
confidence: 58%
See 1 more Smart Citation
“…ChIP-qPCR at the same six ESC and six EpiC enhancers done for BRG1 validated these results and extended them to HDAC2, which is commonly found in a complex with HDAC1 (Lai and Wade, 2011;Jamaladdin et al, 2014) (Figures S5D and S5E). Consistent with a role for FOXD3 in recruiting as well as maintaining HDAC1 at the FOXD3-bound enhancer sites, HDAC1 was not found at the EpiC enhancers prior to FOXD3 binding (compare Figure 6K to 6L).…”
Section: Foxd3 Also Recruits and Maintains Hdac1/2 At Enhancerssupporting
confidence: 58%
“…IP of FOXD3 showed that FOXD3 protein interacts with HDAC1/2, but not HDAC3, in both ESCs and EpiCs cells ( Figure 6G). As was the case with Brg1, evaluation of published expression data for HDAC1/2 double KO ESCs showed significant overlap in expression changes with Foxd3 KO cells, which was further enriched when considering only genes neighboring the FOXD3 enhancers ( Figure 6H) (Jamaladdin et al, 2014).…”
Section: Foxd3 Also Recruits and Maintains Hdac1/2 At Enhancersmentioning
confidence: 79%
“…HDAC1 overexpression has been reported to be positively associated with cell division, differentiation and tumorigenesis (28)(29)(30). Loss of HDAC1 resulted in a 60% reduction in total HDAC activity and a loss of stem cell viability (28). Consistently, total HDAC activity was also elevated in A549-CHI-R and A549 HDAC1-overexpressed cells.…”
Section: Discussionmentioning
confidence: 82%
“…HDAC1 belongs to class I HDACs, which are the most closely associated with malignant phenotypes (27). HDAC1 overexpression has been reported to be positively associated with cell division, differentiation and tumorigenesis (28)(29)(30). Loss of HDAC1 resulted in a 60% reduction in total HDAC activity and a loss of stem cell viability (28).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent studies have suggested that glycans can contribute to epigenetic gene regulation as modulators. For example, a Bcarbohydrate-like^ molecule, inositol tetraphosphate (IP4; inositol 1, 3, 4, 5– tetrakisphosphate) acts as a stimulator to the activity of class I HDACs (HDAC1/2/3) [1618]. Additionally, OGlcNAcylation has been reported to regulate localization, activity, and stability of many transcription factors, as well as their interactions with other proteins and DNA [19, 20].…”
Section: Introductionmentioning
confidence: 99%